Tissue Expanders in Skin Deficient Ventral Hernias Utilizing Component Separation. Issue 11 (November 2015) - Agullo, Francisco J.; Molinar, Vanessa E.; Molinar, Alonso; Palladino, Humberto
Abstract : Summary: Skin deficient complex ventral hernias are complicated surgical cases that have multimodal approaches. There is no current consensus on the management of those patients who also have concomitant stomas or enterocutaneous fistula. We present 2 cases in which the senior authors were able to apply tissue expanders above and between the abdominal wall in patients with an enterocutaneous fistula or stoma. After expansion and final closure, the patients did not experience recurrent hernias.